2016
DOI: 10.1007/s13277-015-4713-3
|View full text |Cite
|
Sign up to set email alerts
|

ABCE1 plays an essential role in lung cancer progression and metastasis

Abstract: Heat shock protein 27 (Hsp27) is a key chaperone that interacts with over 200 client proteins. The expression of Hsp27 might be correlated with poor outcome in many types of cancer. Previous study indicated that Hsp27 might be an important biomarker in hepatocellular carcinoma (HCC). However, the detailed mechanism is less well understood. The shRNA-mediated silencing of Hsp27 decreased the proliferation, migration and invasion of HCC cells. In a xenograft model, the silencing of Hsp27 reduced tumor progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
1
23
1
1
Order By: Relevance
“…Rapid growth and increased metastatic potential are two basic characteristics of tumor cells. Recent evidence has indicated that ABCE1 is crucial in tumor progression, prognosis and metastasis [7, 9]. Our MTT and clonogenic assay data showed that A549 cells overexpressing ABCE1 grew much faster and formed more pronounced and a larger number of colonies.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Rapid growth and increased metastatic potential are two basic characteristics of tumor cells. Recent evidence has indicated that ABCE1 is crucial in tumor progression, prognosis and metastasis [7, 9]. Our MTT and clonogenic assay data showed that A549 cells overexpressing ABCE1 grew much faster and formed more pronounced and a larger number of colonies.…”
Section: Discussionmentioning
confidence: 53%
“…Although an increasing number of studies has demonstrated the role of ABCE1 in tumor cell development, very little is known about the actual mechanisms [7, 25]. Furthermore, the roles of ABCE1 and its Fe-S clusters in carcinogenesis are still undetermined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that CXCL1 is implicated in GC overall survival. ABCE1 (ATP-binding cassette E1) plays a crucial role in the metastasis and progress of lung cancers, and therefore it has been suggested as a valuable therapeutic target for the management of these cancers [44]. We have demonstrated in this study that ABCE1 is elevated in GC and is an indicator for the prognosis of GC.…”
Section: Discussionmentioning
confidence: 57%
“…The study of Wang showed that CXCL1 is also involved in gastric cancer overall survival. ATPbinding cassete E1 (ABCE1) known to play a crucial role in the metastasis of lung cancers, and therefore, a potential therapeutic target in this seting [70], was also elevated in gastric tumors and predicted the prognosis of patients. …”
mentioning
confidence: 99%